Method for preparing magnesium-lithium alloy high-corrosion-resistance coating through PECVD (plasma enhanced chemical vapor deposition) technology

By forming a hydroxide film layer on the surface of magnesium lithium alloy and depositing a fluorocarbon coating, PECVD technology is used to improve the protective performance of magnesium lithium alloy, solving the corrosion problem of magnesium lithium alloy in humid environments, and achieving efficient and stable protection Effect and simple process.

CN119243126AActive Publication Date: 2025-01-03KUNMING UNIV OF SCI & TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411340095.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-01-03
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

Magnesium lithium alloys are prone to corrosion in humid and salt-containing environments. The protection capacity of traditional anti-corrosion films is limited, and the electroplating process is complex and polluted, making it difficult to maintain stability during long-term use.

Method used

The hydroxide film layer is formed by pretreatment and a fluorocarbon coating is deposited thereon. The uniformity, stability and adhesion strength of the film layer are improved by using PECVD technology to form a high corrosion-resistant coating.

Benefits of technology

It significantly improves the protection effect and protection time of magnesium lithium alloy, reduces the preparation energy consumption, is simple and controllable, and is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243126A_ABST
    Figure CN119243126A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a magnesium-lithium alloy high-corrosion-resistance coating through a PECVD technology, and belongs to the technical field of magnesium-lithium alloy corrosion prevention. The method comprises the following steps: (1) mechanically polishing a magnesium-lithium alloy base material; (2) carrying out ultrasonic vibration washing on the magnesium-lithium alloy; (3) the magnesium-lithium alloy is put into a sodium hydroxide solution to be pretreated, (4) PECVD treatment is conducted on the pretreated alloy, and the PECVD treatment atmosphere comprises mixed gas of carbon tetrafluoride and nitrogen; and (5) after ultrasonic cleaning is conducted on the magnesium-lithium alloy with the corrosion-resistant coating, heating and drying are conducted to accelerate stabilization of the corrosion-resistant coating till the corrosion-resistant coating is completely cured and stabilized, preparation of the magnesium-lithium alloy high-corrosion-resistant coating is completed, and the magnesium-lithium alloy with the stable corrosion-resistant coating is obtained. The magnesium-lithium alloy corrosion-resistant coating prepared by the preparation method disclosed by the invention has excellent compactness and uniformity, high bonding strength with a base material, relatively high corrosion resistance and relatively long protection aging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnesium-lithium alloy anti-corrosion, and relates to a method for preparing a magnesium-lithium alloy high-corrosion-resistant coating by using PECVD technology. Background Art

[0002] Magnesium-lithium alloys have become the first choice for lightweight structural materials due to their extremely low density and excellent specific strength. They are widely used in aerospace, automobile manufacturing, portable electronic devices and other fields. The density of magnesium-lithium alloys is about 30% lower than that of aluminum alloys, making them ideal materials for applications with extremely high weight reduction requirements. However, magnesium-lithium alloys have the significant disadvantage of poor corrosion resistance, especially when serving in humid and salty environments. Magnesium-lithium alloys are prone to pitting, crevice corrosion and stress corrosion cracking, which cause damage to the material surface, affect the mechanical properties of the material, and thus shorten its service life.

[0003] The anti-corrosion treatment of magnesium-lithium alloys is mainly carried out by covering the surface of the alloy with an anti-corrosion film. The traditional methods for forming the anti-corrosion film mainly include chemical conversion film, electroplating, anodizing, etc. Although these methods have improved the corrosion resistance of magnesium-lithium alloys to a certain extent, there are still some problems. For example, the protective ability of chemical conversion film and anodizing film is limited and it is difficult to maintain stability in long-term use; the electroplating process is complicated and prone to environmental pollution.

[0004] Plasma enhanced chemical vapor deposition (PECVD) technology is an emerging coating preparation technology. Compared with traditional film formation methods, it can deposit a denser and more uniform film layer, and the deposition process has less environmental pollution, and has received extensive attention. The density, uniformity, and adhesion strength of the anti-corrosion film layer are proportional to the protective effect of the anti-corrosion film layer. Improving the density, uniformity, and adhesion strength between the film layer and the substrate are all conducive to improving the protective effect of the film layer and extending the protective duration of the film layer. Therefore, it is of great significance to further optimize the film performance, improve the protective effect of the film layer, and extend the protective duration of the film layer based on the preparation of the coating using PECVD technology.

[0005] Therefore, it is necessary to provide a method for preparing a high corrosion-resistant coating of a magnesium-lithium alloy by PECVD technology, and to enhance the protective effect and protection duration of the corrosion-resistant coating of a magnesium-lithium alloy prepared by PECVD technology. Summary of the invention

[0006] In order to overcome the problems in the background technology, the present invention forms a hydroxide film layer on the surface of the magnesium-lithium alloy through pretreatment, and deposits a fluorocarbon coating with high chemical inertness on the hydroxide film layer. On the basis of using PECVD technology to prepare the coating, the uniformity, stability, and adhesion strength to the substrate of the film layer are further improved, thereby improving the protective effect and protection duration of the film layer on the magnesium-lithium alloy.

[0007] In order to achieve the above object, the present invention is implemented by the following technical solutions:

[0008] The method comprises the following steps:

[0009] (1) Mechanically grinding the magnesium-lithium alloy substrate;

[0010] (2) ultrasonically cleaning the magnesium-lithium alloy after mechanical grinding in step (1);

[0011] (3) placing the magnesium-lithium alloy after ultrasonic cleaning in step (2) into a sodium hydroxide solution for pretreatment, so that a uniform hydroxide film layer is formed on the surface of the magnesium-lithium alloy to obtain a pretreated alloy;

[0012] (4) performing PECVD treatment on the pretreated alloy, wherein the PECVD treatment atmosphere includes a mixed gas of carbon tetrafluoride and nitrogen, and under the action of plasma, a dense fluorocarbon coating is formed on the surface of the hydroxide film layer, i.e., a corrosion-resistant coating, to obtain a corrosion-resistant coated magnesium-lithium alloy;

[0013] (5) After ultrasonic cleaning of the magnesium-lithium alloy with the corrosion-resistant coating, heating and drying are performed to accelerate the stabilization of the corrosion-resistant coating until the corrosion-resistant coating is completely solidified and stabilized, thereby completing the preparation of the magnesium-lithium alloy high corrosion-resistant coating and obtaining a magnesium-lithium alloy with a stable corrosion-resistant coating.

[0014] Preferably, in the step (1), the magnesium-lithium alloy substrate is mechanically polished using 3000-7000 mesh sandpaper, and the surface roughness of the magnesium-lithium alloy substrate is polished to 1.5-2.0 μm.

[0015] Preferably, in step (2), the magnesium-lithium alloy substrate is placed in acetone for ultrasonic vibration washing, the ultrasonic vibration washing frequency is 40-60kHz, and the vibration washing time is 30min.

[0016] Preferably, in step (3), the mass concentration of the sodium hydroxide solution is 20%, the pretreatment temperature is 30-50° C., and the pretreatment time is 30 min.

[0017] Preferably, in step (4), the deposition temperature is 150-200° C., the deposition pressure is 4.0-5.0 Torr, the plasma power is 100-300 W, and the deposition time is 45-90 min.

[0018] Preferably, in step (4), the flow rate of carbon tetrafluoride gas is 30-60 sccm, and the flow rate of nitrogen gas is 40-80 sccm.

[0019] Preferably, in step (5), alcohol is used for ultrasonic cleaning, the ultrasonic cleaning frequency is 40-60 kHz, and the cleaning time is 30 minutes.

[0020] Preferably, in step (5), the heating and drying temperature is 40-60°C, and the heating and drying method is intermittent heating and drying. After each heating and drying for 30-60 minutes, the corrosion-resistant coating magnesium-lithium alloy is placed in the air for natural air cooling for 6 hours, and then the next heating and drying is carried out, and this process is repeated until the corrosion-resistant coating is completely cured and stabilized.

[0021] Beneficial effects of the present invention:

[0022] 1. The present invention forms a hydroxide film on the surface of the magnesium-lithium alloy through pretreatment, and deposits a corrosion-resistant coating on the hydroxide film layer. The principle of interfacial chemistry is used to effectively improve the bonding strength between the corrosion-resistant coating and the magnesium-lithium alloy substrate. At the same time, the chemically active interface provided by the hydroxide film layer is used to promote uniform deposition of the corrosion-resistant coating and enhance the stability of the corrosion-resistant coating, so that the corrosion-resistant coating has higher density and uniformity and higher bonding strength with the alloy matrix, thereby improving the protective effect of the corrosion-resistant coating on the magnesium-lithium alloy matrix and extending the protective period.

[0023] 2. The present invention uses a mixture of carbon tetrafluoride and nitrogen as a reaction gas to deposit a fluorocarbon coating as a corrosion-resistant coating. The fluorocarbon coating is an inorganic coating with a high degree of chemical inertness. The coating itself has good stability and corrosion resistance.

[0024] 3. The present invention can complete the deposition of corrosion-resistant coating in a shorter time under lower temperature conditions, which helps to reduce the energy consumption in preparing corrosion-resistant coating. In addition, the process flow is relatively simple and the process is highly controllable, which is suitable for industrial promotion and application.

[0025] 4. The intermittent heating and drying method of the present invention can gradually release the internal stress of the corrosion-resistant coating, prevent the corrosion-resistant coating from cracking or peeling due to long-term heating, so as to improve the overall quality and protective effect of the corrosion-resistant coating finally obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION

[0027] The present invention is further described in detail below in conjunction with specific embodiments.

[0028] The chemical composition of the magnesium-lithium alloy used in the embodiments of the present invention and the comparative examples is shown in Table 1. All chemical reagents not specified in the embodiments of the present invention and the comparative examples were commercially available analytically pure reagents for the experiments.

[0029] Table 1

[0030] Mg Li Other Elements About 85% About 10% About 5%

[0031] Example 1

[0032] In this embodiment, the magnesium-lithium alloy corrosion-resistant coating is prepared by the following method:

[0033] (1) The magnesium-lithium alloy substrate is mechanically polished using sandpaper until the surface roughness of the magnesium-lithium alloy substrate is 1.5 μm.

[0034] (2) After polishing, the magnesium-lithium alloy substrate was placed in acetone and vibrated at an ultrasonic frequency of 60 kHz for 30 min to remove oil and impurities on the surface of the magnesium-lithium alloy to obtain a clean vibrated sample.

[0035] (3) The shaken sample was placed in a sodium hydroxide solution with a mass concentration of 20%, and pretreated at a temperature of 50° C. for 30 minutes. After the treatment, a uniform hydroxide film layer was formed on the surface of the magnesium-lithium alloy, thereby obtaining a pretreated sample.

[0036] (4) The pretreated sample was placed in a PECVD reactor, and the reaction atmosphere was set to a mixed gas of carbon tetrafluoride (CF4) and nitrogen (N2), the carbon tetrafluoride gas flow rate was 60 sccm, the nitrogen flow rate was 80 sccm, the deposition temperature was 200°C, and the deposition pressure was 5.0 Torr. The plasma power was set to 300 W, and the processing time was 90 min to deposit a dense fluorocarbon corrosion-resistant coating on the surface of the magnesium-lithium alloy to obtain a corrosion-resistant coated magnesium-lithium alloy.

[0037] (5) The corrosion-resistant coated magnesium-lithium alloy is placed in alcohol for ultrasonic cleaning at a frequency of 60 kHz and a treatment time of 30 minutes; then it is heated and dried for 60 minutes at a drying temperature of 60°C. After the first heating and drying is completed, the corrosion-resistant coated magnesium-lithium alloy is placed in the air for natural air cooling, and then heated and dried again after 6 hours. The heating and drying is repeated 4 times with 3 intervals in between for a total of 18 hours to ensure that the coating is completely cured and stabilized, thereby obtaining a magnesium-lithium alloy with a stable corrosion-resistant coating.

[0038] The magnesium-aluminum alloy corrosion-resistant coating prepared in this embodiment is dense and uniform, with a coating thickness of about 5-7 μm, good coating adhesion, and firmly combined with the magnesium-lithium alloy substrate.

[0039] After the 72h salt spray test, the magnesium-lithium alloy sample of this embodiment showed no obvious corrosion phenomenon, showing excellent corrosion resistance. And after the mechanical friction and corrosion resistance test, the corrosion-resistant coating still remained in a completely solidified state without falling off or peeling.

[0040] Example 2

[0041] In this embodiment, the magnesium-lithium alloy corrosion-resistant coating is prepared by the following method:

[0042] (1) The magnesium-lithium alloy substrate is mechanically polished using sandpaper until the surface roughness of the magnesium-lithium alloy substrate is 1.8 μm.

[0043] (2) After polishing, the magnesium-lithium alloy substrate was placed in acetone and vibrated at an ultrasonic frequency of 50 kHz for 30 min to remove oil and impurities on the surface of the magnesium-lithium alloy to obtain a clean vibrated sample.

[0044] (3) The shake-washed sample is placed in a sodium hydroxide solution with a mass concentration of 20%, and pretreated at a temperature of 40° C. for 30 minutes. After the treatment, a hydroxide film layer is formed on the surface of the magnesium-lithium alloy to obtain a pretreated sample.

[0045] (4) The pretreated sample was placed in a PECVD reactor, and the reaction atmosphere was set to a mixed gas of carbon tetrafluoride (CF4) and nitrogen (N2), the carbon tetrafluoride gas flow rate was 40 sccm, the nitrogen flow rate was 60 sccm, the deposition temperature was 170°C, and the deposition pressure was 4.5 Torr. The plasma power was set to 200 W, and the processing time was 55 min to deposit a dense fluorocarbon corrosion-resistant coating on the surface of the magnesium-lithium alloy to obtain a corrosion-resistant coated magnesium-lithium alloy.

[0046] (5) The corrosion-resistant coated magnesium-lithium alloy is placed in alcohol for ultrasonic cleaning at a frequency of 50 kHz and a treatment time of 30 minutes; then it is heated and dried for 40 minutes at a drying temperature of 50°C. After the first heating and drying is completed, the corrosion-resistant coated magnesium-lithium alloy is placed in the air for natural air cooling, and then heated and dried again after 6 hours. The heating and drying is repeated 4 times with 3 intervals in between for a total of 18 hours to ensure that the coating is completely cured and stabilized, thereby obtaining a magnesium-lithium alloy with a stable corrosion-resistant coating.

[0047] The magnesium-aluminum alloy corrosion-resistant coating prepared in this embodiment is dense and uniform, with a coating thickness of about 4-6 μm, good coating adhesion, and firmly combined with the magnesium-lithium alloy substrate.

[0048] After the 72h salt spray test, the magnesium-lithium alloy sample of this embodiment showed slight corrosion, and the corrosion resistance of the corrosion-resistant coating was slightly lower than that of Example 1, but its corrosion resistance was still at a good level. After the mechanical friction and corrosion resistance tests, the corrosion-resistant coating still remained in a completely solidified state without obvious peeling.

[0049] Example 3

[0050] In this embodiment, the magnesium-lithium alloy corrosion-resistant coating is prepared by the following method:

[0051] (1) The magnesium-lithium alloy substrate is mechanically polished using sandpaper until the surface roughness of the magnesium-lithium alloy substrate is 2.0 μm.

[0052] (2) After polishing, the magnesium-lithium alloy substrate was placed in acetone and vibrated at an ultrasonic frequency of 40 kHz for 30 min to remove oil and impurities on the surface of the magnesium-lithium alloy to obtain a clean vibrated sample.

[0053] (3) The shaken sample was placed in a sodium hydroxide solution with a mass concentration of 20%, and pretreated at a temperature of 30° C. for 30 min. After the treatment, a thick hydroxide film layer was formed on the surface of the magnesium-lithium alloy, thereby obtaining a pretreated sample.

[0054] (4) The pretreated sample was placed in a PECVD reactor, and the reaction atmosphere was set to a mixed gas of carbon tetrafluoride (CF4) and nitrogen (N2), the carbon tetrafluoride gas flow rate was 30 sccm, the nitrogen flow rate was 40 sccm, the deposition temperature was 150°C, and the deposition pressure was 4.0 Torr. The plasma power was set to 100 W, and the processing time was 45 min to deposit a dense fluorocarbon corrosion-resistant coating on the surface of the magnesium-lithium alloy to obtain a corrosion-resistant coated magnesium-lithium alloy.

[0055] (5) The corrosion-resistant coated magnesium-lithium alloy is placed in alcohol for ultrasonic cleaning at a frequency of 40 kHz and a treatment time of 30 minutes; then it is heated and dried for 30 minutes at a drying temperature of 40°C. After the first heating and drying is completed, the corrosion-resistant coated magnesium-lithium alloy is placed in the air for natural air cooling, and then heated and dried again after 6 hours. The heating and drying is repeated 4 times with 3 intervals in between, for a total of 18 hours. The coating is completely cured and stabilized to obtain a magnesium-lithium alloy with a stable corrosion-resistant coating.

[0056] The magnesium-aluminum alloy corrosion-resistant coating prepared in this embodiment is dense and uniform, and the coating thickness is about 6-8 μm. Micro cracks appear in some areas of the coating.

[0057] After the 72h salt spray test, the magnesium-lithium alloy sample of this embodiment showed only a small amount of corrosion at the crack position, and the overall corrosion resistance of the corrosion-resistant coating can be maintained at a relatively good level. After mechanical friction and corrosion resistance tests, the overall stability of the corrosion-resistant coating is good, and only slight peeling of the corrosion-resistant coating occurs in the crack area.

[0058] Comparative Example 1

[0059] This comparative example adopts the same preparation method as Example 1 to prepare the magnesium-lithium alloy corrosion-resistant coating, with the difference that: this comparative example does not use sodium hydroxide solution to pretreat the magnesium-lithium alloy substrate, and directly deposits the corrosion-resistant coating on the surface of the magnesium-lithium alloy substrate, that is, the corrosion-resistant coating is not deposited on the hydroxide film layer.

[0060] After mechanical friction and corrosion resistance tests, the corrosion-resistant coating of the magnesium-lithium alloy prepared in this comparative example was severely peeled off, and the magnesium-lithium alloy without the protection of the corrosion-resistant coating was severely corroded.

[0061] Comparative Example 2

[0062] This comparative example adopts the same method as Example 1 to prepare the magnesium-lithium alloy corrosion-resistant coating, except that: in this comparative example, a mixed gas of carbon tetrafluoride and methane is used during the PECVD treatment process.

[0063] Compared with Example 1, the corrosion resistance of the corrosion-resistant coating of the magnesium-lithium alloy sample in this comparative example is significantly reduced.

[0064] Comparative Example 3

[0065] In this comparative example, the corrosion-resistant coating of magnesium-lithium alloy is prepared by the same method as in Example 1, except that: in this comparative example, the corrosion-resistant coating magnesium-lithium alloy is continuously dried.

[0066] Compared with Example 1, the corrosion-resistant coating of the magnesium-lithium alloy sample in this comparative example showed corrosion spots and local peeling in the early stage of the salt spray test, and the performance of the corrosion-resistant coating was significantly reduced.

[0067] Comparative Example 4

[0068] In this comparative example, the corrosion-resistant coating of magnesium-lithium alloy is prepared by the same method as in Example 1, except that the PECVD treatment temperature in this comparative example is 400°C.

[0069] The corrosion-resistant coating of the magnesium-lithium alloy sample of this comparative example has cracks and pores immediately after preparation.

[0070] It can be seen from Examples 1-3 that during the preparation of the corrosion-resistant coating, the adjustment of the process parameters has a significant impact on the performance of the final corrosion-resistant coating.

[0071] Compared with Example 1, the bonding strength between the magnesium-lithium alloy corrosion-resistant coating and the magnesium-lithium alloy substrate in Comparative Example 1 is significantly reduced, resulting in serious peeling of the corrosion-resistant coating. This is mainly due to the lack of appropriate interfacial chemical reaction and participation of hydroxyl groups between the magnesium-lithium alloy and the corrosion-resistant coating in Comparative Example 1. In Example 1, the pretreatment of sodium hydroxide forms a uniform hydroxide film, and the hydroxide film forms a stable chemical bond with the metal atoms on the surface of the magnesium-lithium alloy substrate through chemical reaction, such as the oxygen atoms in the hydroxide and the magnesium or lithium elements on the surface of the substrate. The strong metal-oxygen bond (MO bond) enables the hydroxide film layer to be firmly attached to the surface of the magnesium-lithium alloy and provide good bonding force. At the same time, this layer of hydroxide film strengthens the surface polarity of the magnesium-lithium alloy substrate and introduces a large number of hydroxyl groups (-OH). These polar groups can chemically combine with chemical reactants (such as fluorinated gas decomposition products) in the corrosion-resistant coating material to form a strong chemical bond, thereby enhancing the bonding strength between the corrosion-resistant coating and the hydroxide film, and then strengthening the bonding strength between the corrosion-resistant coating and the magnesium-lithium alloy substrate through the hydroxide film. On the contrary, in Comparative Example 1, due to the lack of hydroxide film, the surface of the magnesium-lithium alloy is relatively smooth and lacks active sites, and the corrosion-resistant coating and the magnesium-lithium alloy substrate mainly rely on physical adsorption rather than chemical bonding. The binding force of this physical adsorption is much weaker than the chemical bonding force, resulting in a significant reduction in the bonding strength between the corrosion-resistant coating and the magnesium-lithium substrate, thereby affecting the protective effect of the corrosion-resistant coating on the magnesium-lithium alloy.

[0072] Compared with Example 1, the corrosion resistance of the magnesium-lithium alloy corrosion-resistant coating in Comparative Example 2 is significantly reduced, mainly because when a mixed gas of carbon tetrafluoride and nitrogen is used as the reaction atmosphere for PECVD treatment, the generated coating has good density and uniformity, and the presence of fluoride enhances the corrosion resistance and adhesion of the coating. Although the carbon content in the coating increases and the hardness of the coating is improved after the addition of methane in Comparative Example 2, the brittleness of the coating increases and the density decreases. This irregular carbon distribution makes the coating more prone to cracking under stress, thereby significantly affecting the adhesion and corrosion resistance of the coating. In addition, the presence of methane may cause more pores and defects in the coating, further weakening its protective ability.

[0073] Compared with Example 1, the corrosion resistance and bonding strength of the magnesium-lithium alloy corrosion-resistant coating in Comparative Example 3 are significantly reduced, mainly because continuous drying has a great negative impact on the performance of the corrosion-resistant coating. Although continuous drying shortens the total time of the drying process, the corrosion-resistant coating deposited by PECVD technology is prone to accumulate residual internal stress at high temperatures. Continuous drying will lead to a large temperature difference between the inside and outside of the corrosion-resistant coating, and the solvents and volatile substances inside the corrosion-resistant coating are difficult to be completely discharged, and the residual internal stress cannot be effectively eliminated. These residual internal stresses are prone to cause tiny cracks and voids, resulting in the weakening of the density and adhesion of the corrosion-resistant coating. In addition, the difficulty of temperature control during continuous drying increases, which easily leads to local overheating or uneven curing of the corrosion-resistant coating. Ultimately, the magnesium-lithium alloy corrosion-resistant coating in Comparative Example 3 has corrosion spots and local peeling earlier in the salt spray test. By means of interval drying, the corrosion-resistant coating can be stabilized under relatively mild conditions, thereby enhancing the bonding strength between the corrosion-resistant coating and the magnesium-lithium alloy substrate, discharging residual solvents, and improving the corrosion resistance and durability of the coating.

[0074] Compared with Example 1, the magnesium-lithium alloy corrosion-resistant coating prepared in Comparative Example 4 already has more defects, mainly because the PECVD deposition temperature in Comparative Example 4 is too high, which leads to a decrease in the thermal stability of the fluorocarbon coating, and easily generates cracks and pores, thereby reducing the density and corrosion resistance of the coating. In addition, the magnesium-lithium alloy substrate is sensitive to high temperature. The high temperature environment will aggravate the oxidation of the surface of the magnesium-lithium alloy substrate, weaken the bonding force between the corrosion-resistant coating and the magnesium-lithium alloy substrate, resulting in poor adhesion and easy peeling or falling off. At the same time, excessively high processing temperature may also cause changes in the chemical composition of the corrosion-resistant coating. The molecular structure of the fluorocarbon coating will be destroyed due to thermal decomposition, forming an uneven distribution of corrosion-resistant coating components, which further weakens the protective performance of the coating.

[0075] In summary, the present invention prepares a magnesium-lithium alloy corrosion-resistant coating with high density, uniformity, bonding strength with the substrate, stability, etc. by reasonably controlling the process parameters in the preparation process of the magnesium-lithium alloy corrosion-resistant coating and a highly targeted preparation method, thereby effectively enhancing the corrosion resistance and protective time of the magnesium-lithium alloy corrosion-resistant coating. The process flow is simple, the process is highly controllable, and it is suitable for industrial promotion and application.

[0076] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a high corrosion resistant coating of a magnesium-lithium alloy by PECVD technology, characterized in that: The method comprises the following steps: (1) Mechanically grinding the magnesium-lithium alloy substrate; (2) ultrasonically cleaning the magnesium-lithium alloy after mechanical grinding in step (1); (3) placing the magnesium-lithium alloy after ultrasonic cleaning in step (2) into a sodium hydroxide solution for pretreatment, so that a uniform hydroxide film layer is formed on the surface of the magnesium-lithium alloy to obtain a pretreated alloy; (4) performing PECVD treatment on the pretreated alloy, wherein the PECVD treatment atmosphere includes a mixed gas of carbon tetrafluoride and nitrogen, and under the action of plasma, a dense fluorocarbon coating is formed on the surface of the hydroxide film layer, i.e., a corrosion-resistant coating, to obtain a corrosion-resistant coated magnesium-lithium alloy; (5) After ultrasonic cleaning of the magnesium-lithium alloy with the corrosion-resistant coating, heating and drying are performed to accelerate the stabilization of the corrosion-resistant coating until the corrosion-resistant coating is completely solidified and stabilized, thereby completing the preparation of the magnesium-lithium alloy high corrosion-resistant coating and obtaining a magnesium-lithium alloy with a stable corrosion-resistant coating.

2. The method for preparing a magnesium-lithium alloy high corrosion-resistant coating by PECVD technology according to claim 1, characterized in that: In the step (1), the magnesium-lithium alloy substrate is mechanically polished using 3000-7000 mesh sandpaper, and the surface roughness of the magnesium-lithium alloy substrate is polished to 1.5-2.0 μm.

3. The method for preparing a magnesium-lithium alloy high corrosion-resistant coating by PECVD technology according to claim 1, characterized in that: In the step (2), the magnesium-lithium alloy substrate is placed in acetone for ultrasonic vibration washing, the ultrasonic vibration washing frequency is 40-60kHz, and the vibration washing time is 30 minutes.

4. The method for preparing a magnesium-lithium alloy high corrosion-resistant coating by PECVD technology according to claim 1, characterized in that: In the step (3), the mass concentration of the sodium hydroxide solution is 20%, the pretreatment temperature is 30-50° C., and the pretreatment time is 30 min.

5. The method for preparing a magnesium-lithium alloy high corrosion-resistant coating by PECVD technology according to claim 1, characterized in that: In the step (4), the deposition temperature is 150-200° C., the deposition pressure is 4.0-5.0 Torr, the plasma power is 100-300 W, and the deposition time is 45-90 min.

6. The method for preparing a magnesium-lithium alloy high corrosion-resistant coating by PECVD technology according to claim 5, characterized in that: In the step (4), the flow rate of carbon tetrafluoride gas is 30-60 sccm, and the flow rate of nitrogen gas is 40-80 sccm.

7. The method for preparing a magnesium-lithium alloy high corrosion resistant coating by PECVD technology according to claim 1, characterized in that: In the step (5), alcohol is used for ultrasonic cleaning, the ultrasonic cleaning frequency is 40-60kHz, and the cleaning time is 30 minutes.

8. The method for preparing a magnesium-lithium alloy high corrosion-resistant coating by PECVD technology according to claim 1, characterized in that: In the step (5), the heating and drying temperature is 40-60°C, and the heating and drying method is intermittent heating and drying. After each heating and drying for 30-60 minutes, the corrosion-resistant coating magnesium-lithium alloy is placed in the air for natural air cooling for 6 hours, and then the next heating and drying is carried out, and this is repeated until the corrosion-resistant coating is completely cured and stabilized.

Citation Information

Patent Citations

  • Fluorine-containing anti-bacterial coating layer of metal material surface and preparation method thereof

    CN106756765A

  • Process of providing magnesium and its alloys with a protective surface coating against corrosion

    GB615848A

  • Surface treatment method and optical component

    JP2004035941A

  • Color-treated substrate and color-treatment method thereof

    KR101655039B1

  • Method for Treating the Surface of Magnesium and ItsAlloys

    KR1020070097895A